Econometric Models and Economic Forecasts - Robert S. Pindyck; Daniel L. Rubinfeld (USA McGraw-Hill, 1998)
This well known text helps students understand the art of model building - what type of model to build, building the appropriate model, testing it statistically, and applying the model to practical problems in forecasting and analysis
pt. 1. The basic of regression analysis -- pt. 2. Single-equation regression models -- pt. 3. Multi-equation models -- pt. 4. Time-series models
Keywords: Social Sciences (3GdYdhe GdGLJeGYjIs; Economic forecasting -- Econometric models; Econometrics; General; USA